Gestión de archivos eclesiásticos como herramienta de gestión integral. - Alvarado Alvarado, Evelyn Lisseth (2021)
Por medio Del proyecto educativo se da a conocer las series documentales que tienen mayor interés para la investigación histórica en el Marco de los archivos eclesiásticos. Para ello abordaremos en primer lugar, los diferentes tipos de archivos eclesiásticos existentes para lo cual se Va extrayendo de cada uno de ellos los principales y más representativos en las series documentales que integran su cuadro de clasificación. A la vez se buscan contenidos que pueden ser de mayor utilidad para la gestión integral.The present article wants to announce the documentary series that have major interest for the historical investigation in the frame of the ecclesiastic files. For it we will approach first, the different types of ecclesiastic existing files to be extracting from each of them the principal ones and more representative documentary series that integrate his picture of classification. Later, we will observe which are the contents that can be of major usefulness for the historical investigation or that it is the same thing, will show what we can investigate if we take them as a point of reference each of them.